God, universe and life : (spiritual interpretation of the universe) : a scientific study - Munir, Mohammad, 1895- (New Delhi : Adam Pubs., 2010)
On creation and life from an Islamic point of view; refutation of the theories of Darwin, Freud, etc.
Keywords: Theological anthropology; Islamic cosmology; Creation (Islam); Life -- Origin; Life -- Religious aspects -- Islam